Cross-Bite and Oral-Health-Related Quality of Life (OHRQoL) in Preadolescents Aged 11 to 14 Years Old: A Pilot Case-Control Study - Adrián Curto; Alberto Albaladejo; Alfonso Alvarado-Lorenzo; Álvaro Zubizarreta-Macho; Daniel Curto (MDPI AG, 2023)
Introduction: Malocclusions have a negative impact on oral-health-related quality of life (OHRQoL). Posterior cross-bite is one of the most prevalent malocclusions in the preadolescent population. This study investigated the influence of posterior cross-bites (unilateral or bilateral) on OHRQoL in an 11- to 14-year-old population. Materials and Methods: A pilot case-control study was carried out at the Dental Clinic of the University of Salamanca between 2021 and 2023. A consecutive sample of 120 preadolescent patients aged 11 to 14 years old was recruited. Three groups were analyzed: a control group (no posterior cross-bite) (n = 40), a group with unilateral posterior cross-bite (n = 40), and a group with bilateral posterior cross-bite (n = 40). To analyze the OHRQoL, the Spanish version of the Child Perception Questionnaire (CPQ-Esp11-14) was used. Results: The mean age of the sample was 12.2 years old (±0.96 years). The group of patients with a bilateral posterior cross-bite was shown to have higher scores in all dimensions of the CPQ-Esp11-14, as well as a higher total score. Sex only influenced the oral symptom dimension of the CPQ-Esp11-14 questionnaire; in this dimension, the girls described a greater impact. Age did not influence OHRQoL. Conclusion: The presence of a posterior cross-bite had a negative impact on OHRQoL in the preadolescent population that was studied.